AN EXPLORATORY MIXED METHODS STUDY OF STUDENTS’ CRITICAL THINKING BASED ON SELF-REGULATED LEARNING IN NUMERACY LITERACY PROBLEM SOLVING - Khoiri, Ayu Faiqoh; Linuhung, Nego; Rahmawati, Dwi (Universitas Nahdlatul Ulama Sunan Giri Bojonegoro, 2026)
This study aims to explore students’ critical thinking skills in solving numeracy literacy problems based on their levels of Self-Regulated Learning (SRL). The research employed a mixed-methods approach with an explanatory sequential design, involving 36 eleventh-grade students from a public senior high school in Bojonegoro. Quantitative data were collected through SRL questionnaires and numeracy literacy tests, while qualitative data were obtained from in-depth interviews with students representing high, medium, and low SRL categories. The results reveal a consistent relationship between SRL levels and critical thinking abilities. Students with high SRL demonstrated systematic and reflective critical thinking, encompassing interpretation, analysis, evaluation, and reflection. Students with medium SRL showed adequate analytical and evaluative abilities but were less consistent in reflection, while students with low SRL tended to rely on procedural thinking without re-evaluating their results. This study contributes by providing an exploratory mixed-methods profile of students’ critical thinking across different levels of self-regulated learning in numeracy literacy problem solving. The findings suggest that enhancing self-regulation plays a vital role in fostering students’ critical thinking, particularly in numeracy literacy tasks that require logical reasoning and metacognitive reflection.